PENINGKATAN KOMPETENSI PEDAGOGIK GURU MDTA MELALUI PELATIHAN VARIASI GAYA MENGAJAR - Fuji Pratami; Nur Hamidah Pulungan; Hamdanil Hamdanil (Turast: Jurnal Penelitian dan Pengabdian, 2022)
Teachers in the learning process at MDTA Diya’ul Islamiah Islamiah Tanjung Jae Village have not used viriety of teaching styles to the maximum. So, it affects the activities of students in following the learning process. The purpose of this service is to provide training on viriety of teaching styles to improve the pedagogic competence of teachers at MDTA Diya’ul Islamiah Islamiah Tanjung Jae Village. The method used to solve problems in this service is service learning. The results of this service are (1) the MDTA Diya’ul Islamiah Islamiah teacher in Tanjung Jae Village has been given material on viriety of teaching styles to improve pedagogic competence; (2) MDTA Diya’ul Islamiah Islamiah teachers in Tanjung Jae Village are trained to practice the use of viriety teaching styles in the learning process; and (3) the MDTA Diya’ul Islamiah Islamiah teacher in Tanjung Jae Village has been able to use viriety of teaching styles in the learning process. The conditions found during the implementation of the training on viriety of teaching styles at MDTA Diya’ul Islamiah Tanjung Jae Village were (1) teachers did not know beforehand about viriety of teaching styles; (2) teachers are still clumsy in practicing viriety of teaching styles; and (3) teachers are still unable to practice viriety of teaching styles according to the material being taught. The findings during the training have been evaluated, so that teachers can practice viriety of teaching styles well and maximally. When viriety of teaching styles can be used properly and maximally by teachers in the learning process, it will automatically affect the achievement of learning objectives and increase the teacher's pedagogic competence. After this training is carried out, it is hoped that viriety of teaching styles will continue to be used by teachers. Hopefully, through the implementation of this training, the pedagogic competence of the MDTA Diya’ul Islamiah teacher in Tanjung Jae Village will increase.